Facile synthesis of acyl sulfonamides from carboxyic acids using the Mukaiyama reagent. Issue 3 (17th January 2019) - Chen, Ling; Luo, Guanglin
Graphical abstract: Highlights: Acylsulfonamides were synthesized within 1 h using Mukaiyama reagent(CMPI)/DMAP/TEA method at optimal condition. Method was efficient with broad scope of aryl/heteroaryl and alphatic caboxylic acids. Method tolerated various aliphatic, aryl and heteroaryl sulfonamides. Method was simple to operate at room temperature under atmosphere condition. Abstract: A fast and convenient method using the Mukaiyama reagent was developed to prepare acyl sulfonamides from carboxylic acids and sulfonamides. This methodology is effective for a range of acids and sulfonamides proceeding in moderate to good yields with the majority of reactions complete within one hour under the optimized condition.